Orthopaedic fracture surgery in polytraumatized patients while on extracorporeal membrane oxygenation (ECMO): A report of two cases - Jaquelyn Kakalecik; Amanda M. Frantz; Michael T. Talerico; Thomas A. Krupko; Jennifer E. Hagen; Matthew R. Patrick (Trauma Case Reports)
Extracorporeal membrane oxygenation (ECMO) has become a salvage therapy for patients with severe acute respiratory distress syndrome (ARDS). The management of orthopaedic trauma in ECMO-supported patients with ARDS remains an evolving area of interest. Orthopaedic injuries are often temporized with external fixators, skeletal traction, or splints due to hemodynamic instability as well as concerns of exacerbating underlying pulmonary injury. However, patients requiring ECMO support do not rely on their pulmonary system for oxygenation, the need for delayed fixation may not apply. However, patients utilizing ECMO therapy can have external cardiac and pulmonary support depending on their cannulation strategy, bypassing the need for delayed fixation. We present a case series of two polytrauma patients with ARDS who underwent surgical management of pelvic ring and femoral shaft fractures while receiving ECMO support. Both patients underwent surgical management without complication and were able to be weaned from ECMO and ventilator support postoperatively. These cases highlight the potential benefits to orthopaedic fixation and underscore the need for further clinical research.